The ideology of failed states : why intervention fails / Susan L. Woodward, City University of New York, Graduate Center. - Woodward, Susan L., 1944 September 6- (Cambridge University Press, 2017)
What do we mean when we use the term 'failed states'? This book presents the origins of the term, how it shaped the conceptual framework for international development and security in the post-Cold War era, and why. The book also questions how specific international interventions on both aid and security fronts - greatly varied by actor - based on these outsiders' perceptions of state failure create conditions that fit their characterizations of failed states. Susan L. Woodward offers details of international interventions in peacebuilding, statebuilding, development assistance, and armed conflict by all these specific actors. The book analyzes the failure to re-order the international system after 1991 that the conceptual debate in the early 1990s sought - to the serious detriment of the countries labelled failed or fragile and the concept's packaging of the entire 'third world', despite its growing diversity since the mid-1980s, as one.